Digital echocardiography. - Main, M L; Thomas, J D (Current Opinion in Cardiology, 1998)
Continued improvement in the computer price-to-performance ratio and the adoption of international standards have enhanced the feasibility of completely digital echocardiographic laboratories that were initially described more than a decade ago. Digital archival has distinct advantages over analog recording, including improved laboratory efficiency, capability of side-by-side comparison of current and historical studies, streamlined image storage, and enhanced interinstitution image transfer. Studies have demonstrated that clinical and electronic image compression allows efficient storage of data, without affecting diagnostic accuracy. Finally, digital echocardiography has important telemedicine applications.